Influence of sigmoid plate and dura mater on vascular wall displacement, vibroacoustic/hydroacoustic sources characteristics, and frequency-loudness assessments of venous pulsatile tinnitus: A coupled-computational fluid dynamics study combining transcanal recording investigation - Wang, Xing; Hsieh, Yue-Lin; Xu, Xiaobing; Wang, Wuqing (Frontiers in Bioengineering and Biotechnology, 2022)
Investigations of pulsatile tinnitus (PT) caused by sigmoid sinus wall anomalies (SSWAs) using computational fluid dynamics (CFD) have recently increased in prevalence. However, accurate modeling of anatomical structures regarding sigmoid plate dehiscence and acoustic sources of PT remains lacking. This study incorporates coupled CFD techniques, micro-computed tomography, and scanning electron microscopy to reveal the vibroacoustic and hydroacoustic sources and displacement characteristics of the transverse-sigmoid sinus system. Furthermore, the in vivo transcanal-recording technique combined with ipsilateral internal jugular vein compression was implemented to cross-reference the captured acoustic profile of PT with the calculated results. In this study, the transient state coupled CFD technique was used to calculate the vibroacoustic and hydroacoustic sources. The dehiscent sigmoid plate and periosteal dura mater were then reconstructed. The displacement characteristics and acoustic results were analyzed. The displacement of the vascular wall underneath the dehiscent area was 9.6 times larger than that of the sigmoid plate and 3617 times smaller than that of the vascular wall without the overlying osseous structures. The peak amplitude of flow-induced vibroacoustic noise was 119.3 dB at 20.2 Hz measured at the transverse sinus. Within the observed 20 to 1000 Hz frequency range, the largest peak amplitude of hydroacoustic noise was 80.0 dB at 20.2 Hz located at the jugular bulb region. The simulated results conformed with the in vivo acoustic profile which the major frequency of PT falls within 1000 Hz. In conclusion, 1) the sigmoid plate and dura mater greatly impact vascular wall displacement, which should not be overlooked in CFD simulations. 2) By incorporating the transcanal recording technique with IJV compression test, the primary frequency of PT was found fluctuating below 1000 Hz, which matches the frequency component simulated by the current CFD technique; amplitude-wise, however, the peak amplitude of in vivo pulse-synchronous somatosound measures approximately 10 dB, which is comparatively lesser than the CFD results and the subjectively perceived loudness of PT. Thus, the transmission pathway, intramastoid acoustic impedance/amplification effect, and the perceptive threshold of PT require further investigations to minimize the incidence of surgical failure.